Computer-Based Neuropsychological Rehabilitation - Dores, Artemisa Rocha (2019)
[Neurocognitive rehabilitation of people with acquired brain injury (ABI) is a part of neuropsychological rehabilitation that has gained increased interest in response to the growing incidence of this type of injury and to the possibility of post-injury survival, often associated with physical and cognitive deficits, as well as emotional and behavioral changes. These problems call for the need of innovative interventions that can overcome the limitations of traditional approaches to ABI.]